2007
DOI: 10.1523/jneurosci.2476-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Differential Synaptic Integration of Interneurons in the Outer and Inner Molecular Layers of the Developing Dentate Gyrus

Abstract: The dentate gyrus (DG) undergoes continued reorganization and lamination during early postnatal development. Interneurons with anatomically identified synaptic contacts migrate from the outer to the inner regions of the molecular layer (ML) of the DG. By using the 2Ј,3Ј-cyclic nucleotide 3Ј-phosphodiesterase (CNP)-enhanced green fluorescent protein transgenic mouse, we were able to target and physiologically characterize Dlx2 ϩ developing ML interneurons. We investigated whether synapses on migrating ML intern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…This finding was consistent with other researchers [23], who observed that the DG underwent continued reorganization and lamination during early postnatal development in the mouse. This finding was consistent with other researchers [23], who observed that the DG underwent continued reorganization and lamination during early postnatal development in the mouse.…”
Section: Histogram 10supporting
confidence: 94%
“…This finding was consistent with other researchers [23], who observed that the DG underwent continued reorganization and lamination during early postnatal development in the mouse. This finding was consistent with other researchers [23], who observed that the DG underwent continued reorganization and lamination during early postnatal development in the mouse.…”
Section: Histogram 10supporting
confidence: 94%
“…EGFP + cells were identified as described previously (Chittajallu et al, 2004 and 2007). The present study targeted faint EGFP + interneurons and associated (“satellite”) bright EGFP + NG2 + cells in the hilus of the dentate gyrus (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…In this mouse, NG2 + cells can be readily identified based on their higher levels of EGFP fluorescence (Chittajallu et al, 2004; Chittajallu et al, 2005), their unique stellate morphology, and their electrophysiological membrane properties (Chittajallu et al, 2004). Conversely, in the same mouse strain, a subpopulation of interneurons express lower levels of EGFP and all the electrophysiological features typical of GABAergic interneurons (Belachew et al, 2003; Aguirre et al, 2004; Chittajallu et al, 2007). Therefore, this transgenic mouse strain enabled us to identify NG2 + progenitors and GABAergic interneurons, and to perform simultaneous electrophysiological recordings from these cells in the hilus of the dentate gyrus.…”
Section: Introductionmentioning
confidence: 99%
“…The other major subtype of DG interneuron is hilar HIPP cells, which co-express GABA and NPY or somatostatin (for reviews see [55, 81]. However, many other types of DG inter-neurons exist: MOPP cells [28], ivy cells and neurogliaform cells [3] and hilar neurons that innervate the inner molecular layer (HICAP cells; [51, 52]).…”
Section: 2 Gabaergic Transmission In the Normal Adult Dentate Gyrumentioning
confidence: 99%